O napredku in napredkovnem potencialu poznomodernih bivanjskih okoliščin - Sajovic, Špela (Družboslovne razprave, 2009)
The article examines the classic sociological concept of human progress, incorporates new contents based on a reflection of its modern placement and then adapts them to contemporary living conditions. The author realises that the modern concept of progress is unsuitable to man since it derives from the mono-dimensional biological view of human nature. Hence, human happiness is largely perceived from the standpoint of material development. However, the human being is a species capable of moving beyond natural instincts thanks to its instinctive insufficiency due to which its happiness is also placed outside of the materialist sphere, within the state of self-actualisation as the only state which is aligned with human nature or its original openness to the world. The author also recognises late modern living conditions are aligned with human nature and thus advanced since they, given the facts of material security and relative independence of structural constraints, encourage the individual in the direction of self-reflection, greater autonomy and consequently boost the chances of the development of self-realised, happy people.
Keywords: Napredek; Progress; Human nature; Človekova narava; Happiness; Sreča; Sociological aspects; Sociološki vidik; posameznik; postmodernizem